Real-world study of PD-1/L1 immune checkpoint inhibitors for advanced non-small cell lung cancer after resistance to EGFR-TKIs - Wei, Kunchen; Zhou, Chao; Chen, Yang; Feng, Xiao; Tang, Hao (Frontiers in Oncology, 2023)
Background: Programmed cell death-1 (PD-1) and its ligand 1 (PD-L1) inhibitors have achieved good efficacy and safety in patients with advanced EGFR mutation-negative non-small cell lung cancer (NSCLC), but their efficacy in patients with previous EGFR mutations is limited. The aim of the present study was to explore the efficacy of PD-1/L1 immune checkpoint inhibitors for the treatment of patients with advanced NSCLC who are resistant to EGFR-TKIs Methods: This retrospective study included 123 patients with stage IV NSCLC who received treatment in Shanghai Changzheng Hospital between January 2019 and January 2022 after failure of first-line EGFR-TKIs. Of them, 39 received ICIs + chemotherapy and anti-angiogenic drugs (ICIs+BCP group), 51 received ICIs monotherapy (ICIs group), and 33 received chemotherapy and anti-angiogenic drugs (BCP group). The gender, age, smoking history, ECOG score, EGFR mutation type, PD-L1 TPS expression, and the first routine blood index before second-line treatment of all enrolled patients were recorded, and their clinical outcomes and prognosis factors were analyzed.Results: There was no significant difference in the objective response rate (ORR) and disease control rate (DCR) between the three groups.Patients in ICIs+BCP group had better prognosis than those in ICIs monotherapy group (PFS:9.5 vs. 4.64 months, p<0.001; OS: 16.97 vs. 7.9 months p<0.001) or BCP group (9.5 vs. 6.48 months, p<0.005; OS: 16.97 vs.11.39 months p<0.005).Our findings suggest that in the real-world practice in China, PD-1/L1 immune checkpoint inhibitors combined with chemotherapy and anti-angiogenic drugs are effective for the treatment of patients with advanced NSCLC who are resistant to EGFR-TKIs.